Analisis Hubungan Aspek Spiritual Dengan Tingkat Kualitas Hidup Lansia Kabupaten Gorontalo - Elsa Rosemalla (Observasi : Jurnal Publikasi Ilmu Psikologi, 2023)
According to WHO (2019), in the Southeast Asia region the elderly population is 8% or around 142 million people. In 2050 it is estimated that the elderly population will increase 3 times from 2013. In 2000 the number of elderly is around 5,300,000 (7.4%) of the total population, while in 2010 the number of elderly is 24,000,000 (9.77%) of the total elderly reached 28,800,000 (11.34%) of the total population. Data from the Central Bureau of Statistics shows that the elderly population in Indonesia in 2007 amounted to 18.7 million people, then in 2010 it increased to 23.9 million people (9.77%). In 2020 it is predicted that the number of elderly people will reach 28.8 million (11.34%). Based on data from the Republic of Indonesia Ministry of Health (2019), Indonesia is entering a period of aging population, where there is an increase in life expectancy followed by an increase in the number of elderly people. Indonesia has experienced an increase in the number of elderly people from 18 million people (7.56%) in 2010, to 25.9 million people (9.7%) in 2019, and is expected to continue to increase in 2035 to 48.2 million people (15.77%).